Efektifitas Ekstrak Lidah Mertua (Sansevieria trifasciata var laurentii) Sebagai Antifungi Candida albicans - Prasasti Kusumaning Paramastri; Muhammad Taufiq Qurrohman (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2022)
Candidiasis is a disease caused by Candida albicans, this disease has a mortality rate of > 25%, mainly affecting adults, with a frequency of women 2 - 3 times more than men (Raningsih et al., 2018). A commonly used fungi drug is ketoconazole. but it has many side effects so it is necessary to find for alternatives to natural ingredients, namely the leaf of lidah mertua (Sansevieria trifasciata var laurentii) because it contains compounds saponins, flavonoids, triterpenoids, and steroids as antifungals The leaf of lidah mertua were extracted by maceration technique. The purpose of this research was to determine the effect of antifungi of ethanol extract the leaf of Lidah Mertua (Sansiviera trifasciata var Laurentii) against the fungus Candida albicans. This research was experimental using the disc diffusion method with a spread plate technique in the inhibition zone formed at concentrations of 25%, 20%, 15%, 10%, 5%, positive control and negative control. The results of the One way Anova test is known that differ significantly. From the results of this research, it can be concluded that the ethanol extract of the leaves of the leaf of lidah mertua (Sansevieria trifasciata var laurentii) has an effect on the antifungal activity of Candida albicans Keywords       : Candida albicans, Leaf of Lidah Mertua, Antifungal, Ketokonazole